Assessment of listing and categorisation of animal diseases within the framework of the Animal Health Law (Regulation (EU) No 2016/429): Trypanosoma evansi infections (including Surra). (21st July 2017) - ; More, Simon; Bøtner, Anette; Butterworth, Andrew; Calistri, Paolo; Depner, Klaus; Edwards, Sandra; Garin‐Bastuji, Bruno; Good, Margaret; Gortázar Schmidt, Christian; Michel, Virginie; Miranda, Miguel Angel; et al.
Abstract: Trypanosoma evansi infections (including Surra) have been assessed according to the criteria of the Animal Health Law (AHL), in particular criteria of Article 7 on disease profile and impacts, Article 5 on the eligibility of T. evansi infections (including Surra) to be listed, Article 9 for the categorisation of T. evansi infections (including Surra) according to disease prevention and control rules as in Annex IV and Article 8 on the list of animal species related to T. evansi infections (including Surra). The assessment has been performed following a methodology composed of information collection and compilation, expert judgement on each criterion at individual and, if no consensus was reached before, also at collective level. The output is composed of the categorical answer, and for the questions where no consensus was reached, the different supporting views are reported. Details on the methodology used for this assessment are explained in a separate opinion. According to the assessment performed, it is inconclusive whether T. evansi infections (including Surra) can be considered eligible to be listed for Union intervention as laid down in Article 5(3) of the AHL because there was no full consensus on the criterion 5 A(v). Consequently, the assessment on compliance of T. evansi infections (including Surra) with the criteria as in sections 4 and 5 of Annex IV of the AHL, for the application of the disease prevention and control rules referred to in points (d) and (e) of Article 9(1) is also inconclusive, as well as which animal species can be considered to be listed for T. evansi infections (including Surra) according to Article 8(3) of the AHL.